The History of China–Japan Relations From Ancient World to Modern International Order - Bu, Ping; Kitaoka, Shinichi (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
XII, 361 p. 2 illus., 1 illus. in color.